Liberalism and its practice - Avnon, Dan; De-Shalit, Avner (Routledge : Taylor & Francis, 2005)
Liberalism and its Practice brings together leading authorities who provide an excellent insight into the meaning and practice of liberalism. This book explores current debates surrounding liberalism at the end of the twentieth century and what it has to offer in practice. Its focus is two of liberalism's greatest emerging challenges: multiculturalism and states struggling with the transition to democracy. It considers considers the significant tensions that these pressures bring to liberal frameworks and asks what the viable alternatives are.